The Development and Characterisation of Antibodies to Human Factor VIII in Haemophilic Dogs - Littlewood, Janet D; Barrowcliffe, T W (Thrombosis and Haemostasis, 1987)
Four haemophilic dogs received infusions of human factor VIII concentrates, and developed inhibitors to human F VIII. These inhibitors cross-reacted with canine F VIII with parallel increases and decreases in titre. Cross-reaction was also found to porcine F VIII but changes in titre did not correlate with anti-human and anti-canine titres. These inhibitors were found to be immunoglobulins, and antibodies were detected against other proteins found in concentrates. Kinetic studies showed that in all four dogs the F VIII inhibitors were Type II antibodies. One of the dogs behaved as a “high-responder”, whilst another was more analogous to a “low-responder” patient. Phospholipid protection experiments in vitro demonstrated that some antibodies could be prevented from inhibiting F VIII, and porcine F VIII was particularly well protected against inhibition.
Keywords: Haemophilia A; Dogs; Factor VIII concentrates; Phospholipids; Factor VIII inhibitors; Factor VIII antibodies